Mediating role of core total quality management in the relationship between infrastructure total quality management and organizational performance of public Hospital in Pakistan - Maqbool, Muhammad Qasim (2019)
Health care organizations in developing countries face great challenges from both inside and outside the organization. In light of this, the contribution of total quality management (TQM) is extremely valuable for health care organizations to overcome these challenges. Drawing upon resource based view (RBV) of the firm; this study examines the mediating role of core TQM on the relationship between infrastructure TQM and performance of public hospitals in Pakistan, and moderating role of national culture on the link between core TQM and performance of public hospitals in Pakistan. This study applied a hypo deductive research approach. Using cross sectional data, a total 378 valid questionnaires were collected to confirm the proposed hypothesis by using partial least square (PLS) path modeling approach a variance based structural equation modeling technique (SEM). Statistical results show that infrastructure TQM is positively related to core TQM. Core TQM is also found to be positively related to organizational performance. Moreover, results reveal that core TQM mediates the relationship between infrastructure TQM and organizational performance. However, no significant result is found for the moderating effect of national culture on the relationship between core TQM and organizational performance. For theoretical and practical contribution this study contributes to the RBV by providing empirical evidence to support the assertion of the theory. Therefore, this study can also help the physicians, surgeons, pharmacist and health professionals to contribute their services to gain organizational performance. Finally, the limitations and suggestions for future research this study restraints the sample that was taken from the public hospitals of Pakistan and cannot be generalized to the other service organizations.